A retrospective audit of antibiotic prescriptions in a Lebanese Hospital - Ibrahim, Mohamad; Bazzi, Zeinab (International Journal of Infection Control, 2019)
Despite the frequent alarms that have been published about the adverse effects of antibiotic use and misuse, physicians prescribe to patients approximately fifty percent of unnecessary antimicrobials. In an attempt to decrease the emergence of antimicrobial resistance and increase awareness, a team approach is required to address this prescribing phenomenon in a feasible manner. A retrospective study was done at a one-hundred-forty-bed hospital with a representative sample size of 368 patients. Patient data was collected and analyzed by a stewardship team. The overall antibiotic inappropriate rate was 45.8%, which is relatively high and consistent with the findings of other studies mentioned in the literature. This study aimed to provide baseline epidemiological data on the use of antibiotics in a Lebanese hospital and has revealed several notable patterns of antibiotic prescribing practices among Lebanese physicians such as the use of antimicrobial drugs example penicillin was consistently high. Strong correlations were identified between the type of attending physician and antibiotic appropriateness. These findings will be important in constructing an antimicrobial stewardship program to reduce antibiotic misuse.